Assessment of the financial management of the large supermarkets in Colombia 2014-2020 - Rivera - Godoy, Jorge Alberto (Universidad Francisco de Paula Santander, 2021)
Evaluate the financial management of large supermarkets in Colombia in the period 2014-2020, using as a methodology the static and trend analysis of indicators of accounting origin and value management that determine their financial effectiveness and residual profit is the purpose of this research. It is discovered that the large company in this sector achieves equity returns in three years, and its behavior is supported primarily by the efficiency in controlling expenditures; but it has residual losses in all years; This is because the profitability of the operating net assets is lower than the profitability that investors aspire for the risk incurred. What is found is different from what is presented in companies in similar sectors in the United States of America and in emerging economies where equity returns are achieved, and residual profits are achieved each year. This study could be complemented with work on groups of organizations that had a more similar profile in terms of their age, phase of their life cycle, legal structure, and region.